Given:
The mean age of 5 people in a room is 26 years.
A person enters the room. The mean age is now 33.
To find:
The age of the person who entered the room.
Solution:
Formula for mean:
![\text{Mean}=\dfrac{\text{Sum of observations}}{\text{Number of observations}}](https://tex.z-dn.net/?f=%5Ctext%7BMean%7D%3D%5Cdfrac%7B%5Ctext%7BSum%20of%20observations%7D%7D%7B%5Ctext%7BNumber%20of%20observations%7D%7D)
The mean age of 5 people in a room is 26 years.
![26=\dfrac{\text{Sum of ages of 5 people}}{5}](https://tex.z-dn.net/?f=26%3D%5Cdfrac%7B%5Ctext%7BSum%20of%20ages%20of%205%20people%7D%7D%7B5%7D)
![26\times 5=\text{Sum of ages of 5 people}](https://tex.z-dn.net/?f=26%5Ctimes%205%3D%5Ctext%7BSum%20of%20ages%20of%205%20people%7D)
![130=\text{Sum of ages of 5 people}](https://tex.z-dn.net/?f=130%3D%5Ctext%7BSum%20of%20ages%20of%205%20people%7D)
The mean age is now 33. It means, the mean age of 6 people is 33.
![33=\dfrac{\text{Sum of ages of 6 people}}{6}](https://tex.z-dn.net/?f=33%3D%5Cdfrac%7B%5Ctext%7BSum%20of%20ages%20of%206%20people%7D%7D%7B6%7D)
![33\times 6=\text{Sum of ages of 6 people}](https://tex.z-dn.net/?f=33%5Ctimes%206%3D%5Ctext%7BSum%20of%20ages%20of%206%20people%7D)
![198=\text{Sum of ages of 6 people}](https://tex.z-dn.net/?f=198%3D%5Ctext%7BSum%20of%20ages%20of%206%20people%7D)
Now, the age of the person who entered the room is
Required age = Sum of ages of 6 people - Sum of ages of 5 people
= ![198-130](https://tex.z-dn.net/?f=198-130)
= ![68](https://tex.z-dn.net/?f=68)
Therefore, the age of the person who entered the room is 68 years.
Hey there, Lets solve this step by step
<span>The probability of choosing the shaded region is equal to the fraction of the total area that the shaded region is 18 / 50 .
</span>
Formula = Area of unshaded region = Total rectangle Area − Shaded area
Answer = (D)
Step-by-step explanation:
x = 36
y = 48
z = 72
hope it helps
Answer:
Please check the explanation.
Step-by-step explanation:
Let the coordinates of the point F be (x, y).
When a point F(x, y) is reflected over the x-axis, the x-coordinate of the point F remains the same, and the y-coordinate of the point reverses the sign.
Thus, the rule of reflection over the x-axis:
F(x, y) → F'(x, -y)
Here,
F'(x, -y) would be coordinates of point F after the reflection over the x-axis.
Let say, the point F(1, 2).
The coordinate of the point F after the reflection over the x-axis would be:
F(1, 2) → F'(1, -2)
Thus, F'(1, -2) would be the coordinates of point F after the reflection over the x-axis.